Mūzikas nošu attēlu priekšapstrāde optiskiem mūzikas atpazīšanas rīkiem - Brauers, Andris (Latvijas Universitāte, 2024)
Šī bakalaura darba mērķis bija uzlabot Optiskās Mūzikas Atpazīšanas (OMA) sistēmu efektivitāti, kas ir svarīgi, lai pārvērstu mūzikas nošu attēlus digitālā formātā. Tas ir nozīmīgi mūziķiem, lai viņi varētu vieglāk labot un dalīties ar mūzikas notīm. Tomēr OMA sistēmu precizitāte lielā mērā ir atkarīga no attēlu kvalitātes. Tāpēc šajā darbā tika izpētīta dažādu attēlu priekšapstrādes tehniku - krāsu korekcijas, trokšņa noņemšanas, rotācijas un perspektīvas korekcijas un nošu līniju segmentācijas - ietekme uz OMA rīku precizitāti. Pētījuma rezultāti bija dažādi. Krāsu korekcija un trokšņa noņemšanas rezultāti bija nepastāvīgi, kas liecina, ka to efektivitāte var būt atkarīga no situācijām. Savukārt rotācijas un perspektīvas korekcijas parādīja ievērojamu uzlabojumu OMA rīku precizitātē, kas uzsver pareizas attēla orientācijas nozīmi OMA darbībai. Segmentācijas ietekme uz atpazīšanas precizitāti palika nenoteikta, norādot uz turpmākas izpētes nepieciešamību. Šie rezultāti norāda uz dažu attēlu priekšapstrādes tehniku, īpaši attēla orientācijas korekcijas, nozīmi, lai uzlabotu OMA rīku precizitāti. Tomēr analizējot rezultātus jāņem vērā pētījuma ierobežojumi, piemēram, mākslīgi radītie attēlu izkropļojumi, kas koncentrējās tikai uz specifiskām situācijām. Nākotnes pētījumu virzieni varētu ietver plašāku izpēti, iesaistot vairāk OMA rīku, reālus attēlu apstākļus un sarežģītākas muzikālās kompozīcijas. Atslēgvārdi: Optiskā Mūzikas Atpazīšana, Attēlu Priekšapstrāde, Krāsu Korekcija, Rotācijas Korekcija, Perspectīves Korekcija.

This thesis looks into enhancing Optical Music Recognition (OMR) systems, which are used for converting music sheet images into digital formats that can be edited with software. Digital conversion is useful for musicians and enthusiasts, allowing for easier manipulation and sharing of music. However, the inputs images quality significantly influence the accuracy of OMR systems. Thus, this study examines the impact of various image preprocessing techniques, such as color correction, noise removal, rotation and perspective correction, and staff line segmentation. The research methodology involves evaluating the impact of these preprocessing techniques on two selected OMR tools, Oemer and Audiveris. A test dataset containing music sheet images with intentional distortions that mimic real-world issues was created. Developed preprocessing algorithms were then applied to these images, and the improvement in recognition accuracy was assessed by comparing the OMR tools' output against a standard undistorted image output. The study's outcomes reveal varied results across the different preprocessing algorithms. While color correction and noise removal did not consistently improve OMR accuracy, suggesting their effectiveness may be dependent on situation. Rotation and perspective corrections were notably beneficial, particularly for the Oemer tool. This underlines the need for proper image orientation in optimizing OMR performance. The effect of segmentation in improving recognition accuracy remains inconclusive, indicating a potential area for further investigation. These findings highlight the significance of certain preprocessing techniques, especially those related to image alignment, in significantly enhancing OMR accuracy. Such insights are valuable for OMR system developers and users, creating the optimization of preprocessing steps to achieve better recognition results. However, the research has limitations that needs to be taken into account when interpreting the findings, such as the simulated nature of the distortions, the focus on only two OMR tools and evaluation method. Future directions for research include broader exploration involving more OMR tools, real-world image conditions, and complex musical pieces. Investigating advanced machine learning approaches for preprocessing might uncover new methods to improve OMR accuracy further. Additionally, adopting a more musically focused evaluation framework could offer deeper understanding of preprocessing's qualitative impact on music sheet recognition. Keywords: Optical Music Recognition, Image Preprocessing, Color Correction, Rotation Correction, Perspective Correction.
Music Sheet image Preprocessing for Optical Music Recognition Tools
Keywords: Datorzinātne